Computational study of conjugate heat transfer and entropy generation of hybrid nano-particles in an enclosure with solid block - Shahid Ullah; Ghulam Saddiq; Afraz Hussain Majeed; Hammad Alotaibi; Ahmed S. Hendy; Mohamed R. Ali (Case Studies in Thermal Engineering)
A conducting hollow cylinder body is positioned in the center of a horizontal layer of fluid that is heated mixed half vertically and cooled from below and above, representing the physical model under consideration. The purpose of this paper is to investigate conjugate heat transfer of mixed convection and entropy generation of nanofluid in the presence of an external magnetic field via computational approach in an enclosure with a solid block. The thermal conductivities of the body are carefully varied from 0.2 to 5. In addition, a square conducting body is meticulously analyzed using a multi-domain approach. A robust comparison is drawn between the behavior of conducting bodies and adiabatic and neutral isothermal bodies. Notably, for a dimensionless thermal conductivity of 5, the patterns of fluid flow, isotherms, and the associated Nusselt number exhibit an 11 % error compared to an adiabatic body. Additionally, when the dimensionless thermal conductivity is set to 5, the characteristics and Nusselt numbers clearly resemble those of a neutral isothermal body. Furthermore, the results are swiftly contrasted with pure natural convection at a dimensionless thermal conductivity of one.